PENGARUH LITERASI KEUANGAN, MANAJEMEN KEUANGAN DAN PENDAPATAN TERHADAP MINAT INVESTASI EMAS MAHASISWA PENDIDIKAN AKUNTANSI UNIVERSITAS NEGERI SURABAYA - Oda, Firdaus Rafi; Rohayati, Suci (Universitas Islam Negeri Alauddin Makassar, 2023)
Although the form of investment is a precious gold investment, gold investment is part of long-term investment, high risk, many situations, and uncertainty. This is due to the lack of literacy / understanding of gold investment. Thus, this study aims to determine the effects of financial ability, financial management, and interest in money investment. This study uses a quantitative study method. The sample used is 80 student of accounting educational at Surabaya University. Sampling by random sampling method. This survey data was obtained through the distribution of online surveys via Google Forms. The data is processed by multiple regression analysis. The results showed that financial literacy, financial management and income had a simultaneous effect on the interest in gold investment students of the Accounting Education Study Program of Surabaya State University and each variable freely affected the significant effect on the interest in gold investment students of the Accounting Education Study Program of Surabaya State University.